The Effect of Some Heavy Metals on Kidney Tissue and Function - Asmaa Khalid Matni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research tested the effect of cadmium chloride and lead acetate on kidney function and their impact on kidney tissues. The study included (30) white rats that were randomly divided into (6) groups:- The control group takes plain water orally for 30 days, the group that was given CdCl2 (5 mg/kg) of body weight, the group that was given CdCl2 10 mg/kg of body weight, the group that was given lead acetate 50 mg/kg of body weight, the group that was given lead acetate 100 mg/kg of body and the group that was given cadmium chloride 5mg/kg with lead acetate 50 mg/kg body weight with drinking water for a month .The results shown in Table (1) indicated a significant increase (P < 0.05) in the levels of urea, creatinine, and uric acid in the serum of groups treated with CdCl2 at doses of 5 and 100 mg/kg, and the groups treated with lead acetate at doses of 50 and 100 mg/kg, as well as the group that received CdCl2 at a dose of 5 mg/kg along with lead acetate at a dose of 50 mg/kg, comparison with the healthy group .As for histological sections, the results showed the following section of the renal of the group treated with cadmium chloride 5 mg/kg shows atrophic renal glomerulus, necrosis of cells lining Bowman’s capsule , necrosis of cells lining the convoluted tubule and a large increase in the space between the glomerulus and the capsule. As for the group treated with high-dose cadmium chloride showing necrosis of cells lining the glomerulus and degeneration of cells lining the renal tubules Fragmentation of the glomerulus. As for the group treated with lead acetate at a dose of 50 mg/kg showing renal glomerulonephrosis, proximal and distal convoluted tubule necrosis, and periglomerular space in an almost normal manner. A section of the kidney of the group treated with with high-dose lead acetate, showing atrophy of some renal glomeruli and congestion of blood vessels and showing blood congestion within the kidney tissue, and decomposition of the cells lining the urinary tubules , Cross-section of the kidney of the group treated with cadmium chloride 5 mg/kg and lead acetate 50 mg/kg body weight Shows destruction of renal glomeruli and swelling of renal tubule cells and necrosis of the kidney tissue with the appearance of hemorrhage Comparison with the healthy group